Meningkatkan Efisiensi Program Bantuan Masyarakat ODF melalui Identifikasi dan Verifikasi di Desa Bengara, Kecamatan Sekatak, Kalimantan Utara - Fadila, Tiwi; Elicukia; Sakinah; Iswaliyah, Rabialda; Supian; Gunawan, Erix; Yunengsih, Yuyun; Sari, Irda; Syahidin, Yuda; Ulfah, Annisa (PADMA, 2024)
The identification and verification program for latrine assistance in Benggara Village is an effort to improve access to proper sanitation for the community. The process involves identifying households in need of assistance, followed by a survey or verification of latrine conditions, and an evaluation of eligibility. Initially, we managed to determine 40 households eligible for assistance. However, after the survey was conducted, only 35 households met the requirements, such as having available materials like boards, cement, and pipes. The implementation of the program involved active community participation and continuous monitoring. The results are evident not only in the improved latrine infrastructure but also in increased community awareness of the importance of good sanitation. This program is expected to serve as an example for similar efforts elsewhere in improving access to proper sanitation for the community.